Analisis Pendapatan Pedagang Sayur Kaki Lima di Pasar Inpres Tanjung Morawa (Studi Kasus: Kecamatan Tanjung Morawa, Kabupaten Deli Serdang) - Riska Aprilia; Retno Astuti; Mitra Musika Lubis (Jurnal Ilmiah Pertanian ( JIPERTA), 2021)
The study was to analyze the income of vegetable street vendors by counting receipts and cost and thereby understanding its revenue, and know the worthiness of street vegetable vendors business in the Inpres Tanjung Morawa market, the study is carried out from September to October 2020. The identification of the study has been defined impressively, considering the location and is the only market in the Tanjung Morawa district, the sampel number 38 street] vegetable vendors mountain traders determined by the non probability method of collecting samples, the primary and secondary data used. Research method used to know revenue, cost, and income use the income analysis method, and to analyze the feasibility of the business using R/C ratio. It’s a street vegetable vendor’s income study is Rp.554,547-‘/Day. Gained the net revenue cost ratio (net R/C ratio) the R/C vaule is greater than the one that is 1,15, based on these result of street vegetable vendors in the inpres Tanjung Morawa market is worth running.